STRATEGI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA BUKITTINGGI DALAM MENINGKATKAN KUALITAS PELAYAN - Julianti, Indah Cikita; Kusdarini, Kusdarini; Putera, Roni Ekha (Jurnal Administrasi Publik dan Pembanguan, 2025)
This research aims to describe and analyse the strategies carried out by the Bukittinggi City Population Office in improving service quality. The method used in this research is qualitative research method with descriptive research design. The data obtained was carried out with data collection techniques in the form of observation, interviews, and documentation. As well as informant selection techniques with Criterion Sampling techniques with a total of 14 informants and data analysis techniques using the Miles and Huberman method, which starts from data collection, data reduction, data presentation and conclusion drawing/verification. Based on the results of the study, it can be concluded that the Bukittinggi City Population and Civil Registration Office carried out several strategies that were useful for improving service quality. The strategies carried out in the form of creating service media that are useful for providing services and information to the public, conducting periodic meetings that are used to evaluate the services provided, monitoring when staff provide services, and coordinating with several agencies to improve service quality, and regarding the implementation of the Bukittinggi City Population and Civil Registration Office strategy in improving service quality as a whole can be said to be good, but it needs improvement in several indicators such as revamping and rejuvenating facilities and infrastructure, increasing socialisation related to online services, and disciplining staff regarding service time after break time.